The microbial community of a terrestrial anoxic inter-tidal zone : a model for laboratory-based studies of potentially habitable ancient lacustrine systems on mars - Curtis-Harper, Elliot (2019)
Evidence indicates that Gale crater on Mars harboured a fluvio-lacustrine environment that was subjected to physio-chemical variations such as changes in redox conditions and evaporation with salinity changes, over time. Microbial communities from terrestrial environmental analogues sites are important for studying such potential habitability environments on early Mars, especially in laboratory-based simulation experiments. Traditionally, such studies have predominantly focused on microorganisms from extreme terrestrial environments. These are applicable to a range of Martian environments; however, they lack relevance to the lacustrine systems. In this study, we characterise an anoxic inter-tidal zone as a terrestrial analogue for the Gale crater lake system according to its chemical and physical properties, and its microbiological community. The sub-surface inter-tidal environment of the River Dee estuary, United Kingdom (53°21′15.40″ N, 3°10′24.95″ W) was selected and compared with available data from Early Hesperian-time Gale crater, and temperature, redox, and pH were similar. Compared to subsurface ‘groundwater’-type fluids invoked for the Gale subsurface, salinity was higher at the River Dee site, which are more comparable to increases in salinity that likely occurred as the Gale crater lake evolved. Similarities in clay abundance indicated similar access to, specifically, the bio-essential elements Mg, Fe and K. The River Dee microbial community consisted of taxa that were known to have members that could utilise chemolithoautotrophic and chemoorganoheterotrophic metabolism and such a mixed metabolic capability would potentially have been feasible on Mars. Microorganisms isolated from the site were able to grow under environment conditions that, based on mineralogical data, were similar to that of the Gale crater’s aqueous environment at Yellowknife Bay. Thus, the results from this study suggest that the microbial community from an anoxic inter-tidal zone is a plausible terrestrial analogue for studying habitability of fluvio-lacustrine systems on early Mars, using laboratory-based simulation experiments.